Decrease of cardiovascular risk in obese patients who participated in a lifestyle medicine program: Disminución del riesgo cardiovascular en pacientes obesos que participaron en un programa de medicina de estilo de vida - Torres-Rodriguez, Eymard (2021)
Lifestyle Medicine in the management of chronic diseases such as obesity is essential to reduce cardiovascular risk and to reverse the disease process (1). Objective: To determine if a Lifestyle Medicine program can reduce cardiovascular risk in obese adults in Colombia. Material and methods: Descriptive observational study cases series type followed for 6 months in a Lifestyle Medicine Clinic. 9 patients were included taking into account 2 measures of cardiovascular risk as a parameter to complete the program. The following measurements were taken: cardiovascular risk using the Pan American Health Organization (PAHO) calculator, Body Mass Index (BMI), lipid profile, history of smoking, history of diabetes, and systolic blood pressure. Results: Of the 9 obese patients, 22% had an intermediate cardiovascular risk and 78% had a low risk at the beginning of the study. After 6 months, it was achieved that 100% of the participants had a low cardiovascular risk; Furthermore, 11% of the patients managed to normalize their blood pressure values ​​and 20% showed a decrease in high blood pressure values. In addition, 22% went from type 3 obesity to type 2 obesity. Finally, through psychological consultation, it was possible to reduce anxiety levels from high to intermediate in at least 44% of the participants. Conclusions: The Lifestyle Medicine program, in a group of obese patients, managed to achieve a low cardiovascular risk, the decrease and normalization of blood pressure figures and reduction in BMI in participants who completed the study.